Experimental study of pore-scale flow mechanism of immiscible CO2 flooding under in-situ temperature-pressure coupling conditions - Tingting Li; Suling Wang; Jinbo Li; Kangxing Dong; Zhennan Wen (PLoS ONE, 2025)
The flow mechanism of CO2 flooding serves as the theoretical foundation for examining the synergic integration of oil recovery and CO2 storage. Immiscible CO2 flooding has attracted considerable research attention due to its simplicity and cost-efficiency. However, minimal studies are available regarding the flow characteristics and EOR mechanism of immiscible CO2 flooding in in-situ temperature-pressure coupling conditions at the pore scale. Therefore, this study employed a modified high-temperature, high-pressure microfluidic system to simulate the in-situ CO2 and water injection processes in a combined temperature-pressure environment and analyze the multiphase flow characteristics in the pores. The injection rate, displacement pressure difference, displacement efficiency, and residual oil distribution were quantitatively analyzed at different pressures. The results indicated higher residual oil clustering after water flooding at the same injection rate. CO2 flooding significantly reduced residual oil clustering and enhanced the oil flooding effect. The multiphase flow dynamics, type of remaining oil in different injection conditions, and flow characteristics of immiscible CO2 flooding were determined. A higher confining pressure interrupted the CO2 flow, which destabilized the displacement front increased the recovery efficiency by 12.9%. Furthermore, a higher injection rate and displacement pressure increased the recovery efficiency by 24.9% and 6.1%, respectively.